Large-Eddy Simulations of Wind-Driven Cross Ventilation, Part 2: Comparison of Ventilation Performance Under Different Ventilation Configurations - Hwang, Yunjae; Gorlé, Catherine (Frontiers in Built Environment, 2022)
Natural ventilation can contribute to a sustainable and healthy built environment, but the flow can be highly dependent on the ventilation configuration and the outdoor turbulent wind conditions. As a result, quantifying natural ventilation flow rates can be a challenging task. Wind tunnel experiments offer one approach for studying natural ventilation, but measurements are often restricted to a few points or planes in the building, and the data can have limitations due to the intrusive nature of measurement techniques or due to challenges with optical access. Large-eddy simulations (LES) can offer an effective alternative for analyzing natural ventilation flow, since they can provide a precise prediction of turbulent flow at any point in the computational domain and enable accurate estimates of different ventilation measures. The objective of this study is to use a validated LES set-up to investigate the effect of the opening size, opening location and wind direction on the ventilation flow through an isolated building. The effects are quantified in terms of time-averaged and instantaneous ventilation flow rates, age of air, and ventilation efficiency. The LES results indicate that, for this isolated building case, the effect of the wind direction is more pronounced than the effect of the size and position of the ventilation openings. Importantly, when ventilation is primarily driven by turbulent fluctuations, e.g. for the 90° wind direction, an accurate estimation of the ventilation rate requires knowledge of the instantaneous velocity field.